2021
DOI: 10.3389/fgene.2021.693916
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and SARS-CoV-2 Variants: Current Challenges and Health Concern

Abstract: The ongoing coronavirus disease 2019 (COVID-19) outbreak in Wuhan, China, was triggered and unfolded quickly throughout the globe by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The new virus, transmitted primarily through inhalation or contact with infected droplets, seems very contagious and pathogenic, with an incubation period varying from 2 to 14 days. The epidemic is an ongoing public health problem that challenges the present global health system. A worldwide social and economic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 126 publications
0
59
0
2
Order By: Relevance
“…SARS-CoV-2 is able to rapidly genetically diversify and can spread internationally through travellers and cause successive outbreaks. SARS-CoV-2 variants cause the COVID-19 disease with different clinical manifestations, even in populations who have previously been exposed to original viruses ( Zeyaullah et al, 2021 ; SeyedAlinaghi et al, 2021 ; Gautret et al, 2021 ). In this study, we compared the demographics, clinical profile, and outcomes of patients infected with different variants that circulated or continue to circulate in the Marseille area, where three major phases have occurred until June 2021.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 is able to rapidly genetically diversify and can spread internationally through travellers and cause successive outbreaks. SARS-CoV-2 variants cause the COVID-19 disease with different clinical manifestations, even in populations who have previously been exposed to original viruses ( Zeyaullah et al, 2021 ; SeyedAlinaghi et al, 2021 ; Gautret et al, 2021 ). In this study, we compared the demographics, clinical profile, and outcomes of patients infected with different variants that circulated or continue to circulate in the Marseille area, where three major phases have occurred until June 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Current research indicates that antibodies produced by vaccines administered to indigenous people respond to these variants; however, more evidence and research is required to confirm this. In various studies, the mutations or their combinations showed diminished neutralizing activity of serum from mRNA-vaccinated people (Diamond et al, 2021;Zeyaullah et al, 2021).…”
Section: Mutationmentioning
confidence: 99%
“…A principios de 2020, apareció una mutación D614G en el gen que codifica la proteína spike del SARS-CoV-2. La mutación D614G sustituyó gradualmente a la cepa original de SARS-CoV-2 descubierta en China y se convirtió en el tipo dominante del virus que circula en todo el mundo (10) . Hay pruebas emergentes de que la variante B.1.1.7 (Alpha) observada por primera vez en el Reino Unido es más infecciosa que las variantes anteriores y puede ser más virulenta (11) .…”
Section: ¿Qué Hemos Aprendido De La Infección Por Sars-cov-2?unclassified